Photoelectrochemical splitting of water with nanocrystalline Zn1-xMnxO thin films: first-principle DFT computations supporting the systematic experimental endeavor - Sharma, Vidhika; Dixit, Mudit; Satsangi, Vibha R.; Dass, Sahab; Pal, Sourav; Shrivastav, Rohit (International Journal of Hydrogen Energy, 2014)
Photoelectrochemical splitting of water with nanocrystalline Zn1-xMnxO thin films was investigated. ZnO thin films with 1, 3, 5 and 7% at. Mn incorporation were synthesized by sol gel method and characterized by X-Ray Diffraction (XRD) analysis, Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), X-ray Photoelectron spectroscopy (XPS), High Resolution Transmission Electron Microscopy (HR-TEM) and UV-Vis spectroscopy. Mn incorporation coupled with variation in sintering temperature led to significant microstructural changes, which tentatively influenced the magnitude of optical absorption and charge carrier mobility, thereby impacting the performance of such systems towards photoelectrochemical splitting of water. Electronic structure computations based on first principle density functional theory (DFT) revealed electronic states of Mn being responsible for the marginally recorded red shift in bandgap energy. Photoelectrochemical measurements using thin films of 1% at. Mn:ZnO sintered at 600 degrees C yielded 3 times enhanced photocurrent at zero bias due to improved optical absorption. Plausible explanations for the effect have also been offered. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Density functional theory; Hydrogen energy; Mn doped ZnO; Optical properties; Photoelectrochemical water splitting

Influence of carbon and phosphorus doping on electronic properties of ZnO - Sharma, Vidhika; Prasad, Mohit; Jadkar, Sandesh; Pal, Sourav (Journal of Materials Science-Materials in Electronics, 2016)
ZnO is one of the most promising candidate for photoelectrochemical splitting of water for hydrogen production. To increase the efficiency of ZnO based photoelectrochemical cell, its band-gap and band edges should be tailored to match visible light spectra and water redox potential respectively. In this paper, First-principles density functional theory calculations have been performed to evaluate the effect of non-metal dopants on electronic properties of ZnO. The model structures of X-doped ZnO were constructed using 32-atom 2 x 2 x 2 supercell of wurtzite ZnO with one O atom replaced with X (carbon C, phosphorus P). With respect to the electronic band structure, C (2p), P (3p) states are located above the valence band maximum of ZnO and mixing of these states is feeble to produce significant band gap narrowing. Doping of these non-metals dopants helps in the creation of isolated states which enhances visible light absorption of ZnO. Our theoretical calculations are consistent with the experimental results of C (P) doped ZnO and fully explains its visible light activity on non-metal doping.